2015
DOI: 10.1016/j.redox.2015.07.009
|View full text |Cite
|
Sign up to set email alerts
|

Genetic disorders coupled to ROS deficiency

Abstract: Maintaining the redox balance between generation and elimination of reactive oxygen species (ROS) is critical for health. Disturbances such as continuously elevated ROS levels will result in oxidative stress and development of disease, but likewise, insufficient ROS production will be detrimental to health. Reduced or even complete loss of ROS generation originates mainly from inactivating variants in genes encoding for NADPH oxidase complexes. In particular, deficiency in phagocyte Nox2 oxidase function due t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
115
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 136 publications
(127 citation statements)
references
References 258 publications
2
115
0
2
Order By: Relevance
“…Defects in the DUOX2/DUOXA2 heterodimer lead to hypothyroidism and goiter. Since the first report in 2002 of DUOX2 mutations causing CH (10,11), over 40 mutations in the DUOX2 gene have been described correlated with CH, while only four mutations have been identified in the DUOXA2 gene (3,8,9,10). Thus far, our splice site mutation, as far as we know, is identified for the first time as being causative of CH.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Defects in the DUOX2/DUOXA2 heterodimer lead to hypothyroidism and goiter. Since the first report in 2002 of DUOX2 mutations causing CH (10,11), over 40 mutations in the DUOX2 gene have been described correlated with CH, while only four mutations have been identified in the DUOXA2 gene (3,8,9,10). Thus far, our splice site mutation, as far as we know, is identified for the first time as being causative of CH.…”
Section: Discussionmentioning
confidence: 99%
“…The patients with DUOX2 or DUOXA2 mutation show a great genotype-phenotype variability (10,11). Maruo et al (3) firstly reported the p.R885Q mutation in the DUOX2 gene exhibiting transient hypothyroidism, which is not similar to our patient.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These generated ROS are believed to be responsible for destroying the engulfed pathogens in the phagolysosome. Mutation in genes encoding for NADPH oxidase complexes resulting in insufficient ROS production that is a direct cause of chronic granulomatous disease (CGD) [92]. CGD is a rare inherited immune disorder caused from the inability of phagocytes to kill the ingested microbes, and its typical manifestation is frequently recurrent subcutaneous abscess formation together with hyperinflammation.…”
Section: Roles Of Ros In Physiology and Pathologymentioning
confidence: 99%
“…The superoxide anion is the precursor of the so-called Reactive Oxygen Species (ROS) which serve as microbicide weapons. The physiological importance of the phagocyte NADPH oxidase is evidenced by an immunodeficiency disease called chronic granulomatous disease (CGD), in which defective microorganism killing entails recurrent and severe infections (reviewed in [1]). Studies over the last decade revealed homologs of phagocyte NADPH oxidases forming the NOX family [2,3], which enlarged considerably the number of its physiological functions (inflammatory response, post-translational proteins processing, inter-and intra-cellular signaling, regulation of endothelial function, regulation of gene expression and cell differentiation…).…”
Section: Introductionmentioning
confidence: 99%